On the preparation and physicochemical properties of pH-responsive hydrogel nanocomposite based on poly(acid methacrylic)/laponite RDS - Junior, Carlos R.F. [UNESP]; Fernandes, Renan da S. [UNESP]; de Moura, Marcia R. [UNESP]; Aouada, Fauze A. [UNESP] (Elsevier, 2020)
In this paper, a series of novel poly(methacrylic acid)/laponite RDS (PMAA/Lap RDS) nanocomposite hydrogels crosslinked by N,N’-methylene bisacrylamide were synthesized via free radical polymerization by using potassium persulfate as initiator. The main novelty of this paper refers to the detail investigation of how the laponite RDS influenced of the pKa, and consequently, the water-uptake of these nanocomposites. In parallel, the evidence of incorporation and interactions of the materials was confirmed by scanning electron microscopy and Fourier transform infrared spectra techniques. By the X-ray diffraction technique (XRD), it was possible to confirm the exfoliation/intercalation configuration of the nanoclay laponite RDS (Lap RDS) into the PMAA matrix. Hydrophilic properties, measured by swelling degree (SD), indicated that the presence of Lap RDS influenced the water uptake capability of the nanocomposite, reaching a maximum of 91 ± 2 g/g for nanocomposites constituted by 5 % of nanoclay. Besides, the pKa of the nanocomposite can be adjusted by nanoclay content. In this way, the ability of these hydrogels to respond to pH values can be useful to act as trigger in controlled release systems.
Keywords: Hydrogel; Nanoclay; Nanocomposite; pH-responsive; Swelling degree